Synthesis and Luminescent Properties of YPO4:Eu3+ Cornflakes Self-Assembled by Nanocrystals - Lv, Changhe; Zhang, Linyun; Guan, Hangmin; Zhu, Dechun (Asian Journal of Chemistry, 2012)
A large-scale novel YPO4:Eu3+ cornflakes self-assembled by nanocrystals were synthesized by a facile hydrothermal method. X-Ray diffraction results show that the cornflakes are pure tetragonal structure. Transmission electron microscopy and selected area electron diffraction studies indicate that the YPO4:Eu3+ cornflakes are polycrystalline structure with a narrow size distribution. Photoluminescence spectra results demonstrate that the YPO4:Eu3+ cornflakes have two strong 5D0/7F1 (590 nm) and 5D0/7F2 (616 nm) transition peaks corresponding to orange-red and red colour, respectively.